2005
DOI: 10.1007/s10350-005-0045-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive Surgery With Intraperitoneal Chemohyperthermia for the Treatment of Pseudomyxoma Peritonei: A Prospective Study

Abstract: Cytoreductive surgery with intraperitoneal hyperthermic chemotherapy is a feasible treatment for pseudomyxoma peritonei. It is associated with acceptable morbidity when performed by an experienced surgical team. Histologic grade is the major determinant of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 22 publications
2
47
0
4
Order By: Relevance
“…Several factors have been analyzed as predictive factors of moderate to severe morbidity following CRS and HIPEC such as sex [35], age, primary colonic anastomosis, number of peritonectomy procedures [10,14,15,28,42], number of visceral resections [10,14,28], number of anastomosis [10], incomplete cytoreduction, disruption of the umbilical fissure [43], dose of chemotherapeutic agent [15], intra-abdominal HIPEC temperature and histopathologic grade [42].…”
Section: Risk Factors For Complicationsmentioning
confidence: 99%
“…Several factors have been analyzed as predictive factors of moderate to severe morbidity following CRS and HIPEC such as sex [35], age, primary colonic anastomosis, number of peritonectomy procedures [10,14,15,28,42], number of visceral resections [10,14,28], number of anastomosis [10], incomplete cytoreduction, disruption of the umbilical fissure [43], dose of chemotherapeutic agent [15], intra-abdominal HIPEC temperature and histopathologic grade [42].…”
Section: Risk Factors For Complicationsmentioning
confidence: 99%
“…As described by (22). Despite the relatively few genes that were characterized in detail in those previous studies, it is clear that regulatory overlap occurs within H. pylori adaptive responses.…”
Section: Fe-fur Activation: An Under-appreciated Regulatory Mechanismmentioning
confidence: 95%
“…Numerous studies have identified a role for Fur regulation in numerous adaptive responses in vitro, as well as in vivo colonization (22,67) and disease development (111).…”
Section: Dissecting the Roles Of Fe-fur And Apo-fur Regulation In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Results are encouraging with a 5-ys-OS ranging from 62.5 to 100% for low grade PMP and from 0 to 65% for high grade disease . This differentiation is crucial for the evolution of disease; low grade tumours are slow growing and indolent differently from those high grade, fast growing and aggressive (Sugarbaker and Chang, 1999;Witkamp et al, 2001;Güner et al, 2005;Moran et al, 2008;Moran and Cecil, 2003;Murphy et al, 2007;Baratti et al, 2008;Elias et al, 2008;Loungnarath et al, 2005;Smeenk et al, 2007;Stewart et al, 2005;Yan et al, 2006). The goal of the surgical cytoreduction is to remove all the visible tumor by the following procedures: right subdiaphragmatic and parietal peritonectomy, left subdiaphragmatic and parietal peritonectomy,greater omentectomy with splenectomy, lesser omentectomy and stripping of the omental bursa, andpelvic peritonectomy with salpingo-oophorectomy in women.…”
Section: Advanced Oncological Surgery In Pseudomyxoma Peritoneimentioning
confidence: 99%